Peningkatan Kemampuan Menulis Deskripsi melalui Pemanfaatan Media Audio Visual Kelas V - Zuliani, Rizki; Anastasia, Anastasia; Anjani, Delia Putri (ANWARUL, 2023)
This study aims to improve students' description writing skills with audio video media in fifth grade students at SD Negeri Slapajang II. This type of research is classroom action research. The research subjects were fifth grade students. This classroom action research was conducted in two cycles with four components in each cycle, namely planning, action implementation, observation, and reflection. Data collection techniques used were questionnaires, observations (observations), interviews, and description writing tests. The data analysis technique used is a qualitative analysis technique. Criteria for success seen from the process and product. The success of the process is measured based on improving the learning process in a better direction. The success of the product is measured based on KKM achievement and better student scores. The results of this study indicate that the use of audio video media can improve the description writing skills of the fifth grade students of SD Negeri Slapajang II. Improvements can be seen in processes and products. Improving the quality of the process seen in student activities in learning. Improved process quality can be seen from the condition of students who are more active in asking questions, more enthusiastic, and more independent. Process quality improvement has a positive impact on product quality improvement.